PENGARUH MODEL CIRCUIT LEARNING TERHADAP KEMAMPUAN MENULIS TEKS NARASI BERBANTUAN MEDIA MIND MAPPING PADA SISWA KELAS IV MADRASAH IBTIDAIYAH DARUL FALAH SELAKAU - Gita Febrianti; Zulfahita; Evinna Cinda Hendriana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to: 1) determine differences in students' narrative writing abilities. 2) to find out how big the influence of the circuit learning model assisted by mind mapping media is. The type of research design used is a Pre-Experimental design, namely One Group Pre-test Posttest design. The population in this study was all class IV students of Madrasah Ibtidaiyah Darul Fallah Selakau, consisting of 30 class A students and 30 class B students, so a total of 60 people. The sample in this research is a population that is part of the number and characteristics of that population." A good sample is a sample that is representative (represents) the population, so that the conclusions can be applied to the entire population. This research technique uses instruments that support and strengthen information for research, including test questions. The form of this research instrument is in the form of guidelines, including test guidelines which are written down in note form to obtain accurate information. The test for skills in writing narrative text in the form of an essay, data analysis was carried out using the prerequisite tests used in this research, namely the normality test, homogeneity test, hypothesis test and effect size. Based on the data results, it can be concluded that: 1) there is a difference in the ability to write student narratives between students who apply the circuit learning model assisted by mind mapping media and students who do not use the circuit learning model assisted by mind mapping in class IV students at MI Darul Falah Selakau. This difference is marked by the value of t_(count <) t_table, namely 7.66 >28. 2) the influence on the ability to write narratives of students at IV MI Darul Falah Selakau obtained an Effect Size (E_s) value of 86.46, which is classified as high.